Rehabilitation of Open-cast Coal Mines in Singrauli Region of Uttar Pradesh and Madhya Pradesh - Lal, Shyam (Indian Forester, 1994)
The paper deals with planting of suitable tree species and their results for rehabilitation of open cast coal mines in Singrauli region of Uttar Pradesh and Madhya Pradesh.